Postoperative paediatric pain prevalence: A retrospective analysis in a university teaching hospital. (October 2016) - Avian, Alexander; Messerer, Brigitte; Wünsch, Gerit; Weinberg, Annelie; Kiesling, Andreas Sandner; Berghold, Andrea
Abstract: Background: Overall pain prevalence in paediatric patients is well documented, but relatively little attention has been paid to pain prevalence and intensity on specific postoperative days within the first week following an operation. Objectives: To evaluate reported pain prevalence on the day of surgery and each day during the following week and to analyse pain trajectories. Design: Retrospective study. Setting: Single centre university hospital. Participants: 815 postoperative children and adolescents (age ≤ 18 years) were included (female: 36%, age 9.8 ± 5.8). Children with ear, nose, throat (e.g. tonsillectomy), eye (e.g. strabismus repair) or dental surgery (e.g. dental extraction) were treated at other departments and therefore were not included in this study. Methods: Retrospective analysis of the overall and clinically relevant (pain score ≥4/10) postoperative pain prevalence in children and adolescents during the first week after surgery. Possible influencing factors (age, sex, body mass index, type of anaesthesia, type of surgery and duration of surgery) on pain trajectories are analysed using mixed model techniques. Results: Overall, 36% of 815 analysed children and adolescents suffered from pain ≥4 during their entire hospital stay. Compared to the day of surgery, the number of patients with pain ≥4 was slightly higher on day 1 after surgery (21% vs. 25%, respectively). In self-reported pain intensity rating (done for patients age ≥ 4 years) the type of surgery ( p < .001) was the only significant variable influencing pain intensity. In observational pain assessment (age < 4 years) pain scores increased with patient's age ( p = .004). In this patient group, pain intensity ratings did not differ between types of surgery ( p = .278). Conclusion: Type of surgery is an important predictor for self-reported pain intensity ratings in children but not for observational pain assessment in younger children. In younger children observational pain assessment ratings increase with age.